Banning English Language Teaching in Iranian Public Schools: Beneficial or Risky? - Hamid Reza Mahboudi (University of Muhammadiyah Prof. DR. HAMKA, 2020)
Knowledge of English as a means of communication among nations of the world is regarded as a must have asset by everyone in today’s world. However, many scholars and writers advocate the imperialist view arguing that the globalization of English results in an increasing intrusion of English into the lives of people exerting dominance, power, culture, ideology and language of English speaking countries over the periphery countries. Taking up an anti-imperialist stance, the author of this literature critically examines studies completed on EFL students’ attitudes towards learning English language to date and determines how popular English is in Iran in comparison to other foreign languages. After having discovered the popularity of English in Iran, the author argues against the strict anti-intrusion policies of Iranian government which has so far led to proposed bans or tight restrictions on ELT in Iran. The objective is to call on political extremists to moderate their stance on their anti-intrusion policies. The author collected findings from dozens of studies published in post-revolutionary Iran between 1977 and 2019 and concluded that the participants found English learning beneficial and mostly favoured. Findings highlight highly positive attitudes towards learning English that do not fit the linguistic imperialism paradigm. The paper, therefore, argues against linguistic imperialism, its credibility and the many disadvantages that have been linked to it by highlighting a massive influx of respondents' high inclination towards learning English that show a dramatic increase over time and positive expressions on the positive effects of English on the country's social, economic, and scientific growth. Eventually, the paper prescribes negotiation rather than prohibition. Negotiation and respect are beneficial for both sides, for people and government. The views and opinions expressed in this article promise clear implications for government officials, educators, parents, EFL teachers and policy-makers.